Design and Implementation of Markerless Augmented Reality Application for Cockroach Phobia Therapy Using Adaptive Threshold - Fiandra Fatharany; Anny Yuniarti; Ridho Rahman Hariadi (Jurnal Teknik ITS, 2016)
Augmented reality (AR) technology is useful for treating several psychological problems, including phobias such as fear of flying, agoraphobia, claustrophobia, and phobia to insects and small animals. However, the currently existing applications for therapy of cockroach phobia that uses AR technology are still very dependent towards the presence of markers, which might lessen the feeling of being in an actual scenario from everyday lives. In this paper, we created a system that is able to use everyday things as a replacement for markers for phobia therapy for cockroach. There are five main processes: getting the live streaming feed from camera, preprocessing, extracting the center point of the objects, tracking the marker-substitute objects, and lastly, instantiating cockroaches randomly after user lifts the objects according to the number and mode of the cockroaches, whether it is moving or not, that are predetermined by the user. The evaluation in this paper includes eight participants that are carefully selected based on their Fear of Spiders Questionnaire (FSQ) score that is translated into Indonesian and modified to accommodate cockroaches instead of spiders. The results is that the system can induce anxiety level on participants with the highest score of 10, which is the highest score in Standard Unit of Discomfort scale (SUDs). While the presence and reality judgment of this paper has the highest score of 7 which is also the highest score in Slater-Usoh-Steed Questionnaire (SUS).